Filicide-Suicide Involving Children With Disabilities. (June 2013) - Coorg, Rohini; Tournay, Anne
Filicide-suicide, or murder of a child by a parent followed by suicide, has an unknown incidence in both the general and disabled population. As there is no national database, the authors examined known associated factors and newspaper reports to characterize filicide-suicide victims and perpetrators involving children with disabilities. A newspaper search was conducted using LexisNexis and NewsBank: Access World News databases through the University of California, Irvine Library's Web site. Age, gender of child and parent, method used, and diagnoses of parent and child were recorded. Twenty-two news articles were found describing a total of 26 disabled children as victims of filicide-suicide between 1982 and 2010. Eighty-one percent of children killed were male, and 54% were autistic. Thirty percent of perpetrators had a reported mental illness. Male children or children with autism may be at risk for filicide-suicide, but accurate record keeping is needed to determine the incidence and risk factors and aid in its prevention in the disabled population.